2001
DOI: 10.1111/j.1478-4408.2001.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of silk with electron beam irradiation

Abstract: The radiation-induced graft polymerisation of hydroxyethyl methacrylate on silk fabric has been studied using an electron beam irradiation technique. Two irradiation processes, pre-irradiation and coirradiation, were compared, and some factors affecting the degree of grafting were investigated. The physical and mechanical properties such as whiteness, breaking strength and resilience of the radiation-grafted silk fabrics were examined. The hydroxyethyl methacrylate grafting of silk with electron beam irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 5 publications
(3 reference statements)
1
18
0
Order By: Relevance
“…9,32,33 Similarly, TGA curves displayed only one inflection point in the range from 200 to 4008C, but the thermal stability was differently affected by the monomer type, as illustrated in Table VI. In the case of HEMA and BMA, unlike dimethacrylates, the peak of the derivative curve is shifted to higher temperature than untreated fiber, showing a moderate increase of thermal stability.…”
Section: Thermal Analysis Of Grafted Silkmentioning
confidence: 94%
See 1 more Smart Citation
“…9,32,33 Similarly, TGA curves displayed only one inflection point in the range from 200 to 4008C, but the thermal stability was differently affected by the monomer type, as illustrated in Table VI. In the case of HEMA and BMA, unlike dimethacrylates, the peak of the derivative curve is shifted to higher temperature than untreated fiber, showing a moderate increase of thermal stability.…”
Section: Thermal Analysis Of Grafted Silkmentioning
confidence: 94%
“…[8][9][10] Many works on silk grafting have been developed using various vinyl monomers: styrene, 11 acrylamide, 2 methacrylamide, 3,4,10,[12][13][14][15][16][17][18][19][20] N(nbutoxymethyl)methacrylamide, 21,22 methacrylonitrile, 23,24 vinyltrimethoxysilane 25 and several methacrylates: methyl-, [4][5][6][7][8]20,24,[26][27][28][29] ethyl-, 24 isopropyl-, 10 n-butyl-, 30 benzyl-, 31 glycidyl-, 2 2-hydroxyethyl-, 3,4,9,10,18,19,32 ethoxyethyl-methacrylate. 33 Methacrylamide (MAA), however, is the monomer most used in industry because it gives products with soft hand, crease recovery (up to 30% weighting), and increased hygroscopicity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of irradiation on PCL porous scaffolds were also studied as well as the bulk polymer 17, 18. Irradiation is also used as a tool for silk fiber modification and grafting 19–22. Mamedov et al23 and Wang et al24 observed that EPR studies were also used to investigate the formation of free radicals in silk fiber after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Irradiation is also used as a tool for silk fiber modification and grafting. [19][20][21][22] Mamedov et al 23 and Wang et al 24 observed that EPR studies were also used to investigate the formation of free radicals in silk fiber after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with chemical grafting, radiation-induced grafting has many advantages such as no chemical initiators are used and grafting yield can be controlled by controlling dose and the time of irradiation. Shao et al used an electron beam to induce grafting of 2-hydroxyethyl methacrylate (HEMA) on silk fabric (Shao et al, 2001). They showed that the degree of grafting was related to the irradiation dose.…”
Section: Radiation Induced Surface Graftingmentioning
confidence: 99%